MODEL KUANTUM DINAMIKA HARGA SAHAM DALAM WAKILAN INTEGRAL LINTASAN (STUDI KASUS PADA SAHAM PT. ASTRA AGRO LESTARI, TBK.) - Apriniyadi, Mohammad; Palupi, Dwi Satya; Rosyid, Muhammad Farchani (Physics Communication, 2017)
Quantum model of stock price dinamics has been proposed obtained. The solution based on this model is obtained by using path integral representation. The final equations of the model is in the form of Fourier transformation integral. The Fourier transform is applied to determine the form of probability distribution. The model then tested in the case of the real data of the stock price index of PT . Astra Agro Lestari, Tbk. The comparation yield some essential parameters corresponding to the stock price index of PT. Astra Agro Lestari, Tbk